IMPLEMENTATION OF THE CIVILIZATION TEACHINGS OF THE NAQSABANDIYAH TARGET IN THE MODERATION OF RELIGIOUS BEHAVIOR OF TNW DAYAH MUDI FRIENDLY SAMALANGA BIREUN STUDENTS - Marzuki, Datuk Imam; Arianto, Nanang; Masykuro, Fadhlan (Faculty of Law, Universitas Pekalongan, 2024)
This study wants to see the contribution of Islamic boarding schools in fostering attitudes and behavior of religious moderation. Especially Dayah Mudi Mesra Samalanga Bireun Aceh which teaches the Tarekat every month of Ramadan. This is because several previous studies have revealed findings that there is a connection between Islamic boarding schools and violence in the name of religion. This research uses qualitative methods, with a phenomenological approach. And the target of this research is the Mudi Mesra Samalanga Islamic Boarding School, Bireun Regency. The figures who will be interviewed are teachers and students. This study is also to trace and explain the relationship between the implementation of the congregation's practices and attitudes of religious moderation. By analyzing using empiricism and survival theory. In accordance with the title, namely: Implementation of TNW teachings in the religious moderation behavior of students , the practice of the Mudi Mesra Samalanga Islamic Boarding School, Implementation of TNW Teachings in the Context of Tolerance, Implementation of TNW Teachings in the Context of Brotherhood, and Implementation of TNW Teachings in the Context of Simplicity.